Epidemiology of Elbow Dislocations in High School Athletes. (January 2016) - Dizdarevic, Ismar; Low, Sara; Currie, Dustin W.; Comstock, R. Dawn; Hammoud, Sommer; Atanda, Alfred
Background: The elbow is the second most commonly dislocated major joint in the general population. Previous studies that focused on emergency department populations indicate that such injuries occur most frequently among adolescent athletes. Purpose: To describe the epidemiological rates and patterns of sports-related elbow dislocations in high school athletes. Study Design: Descriptive epidemiology study. Methods: Sports-related injury data for the 2005-2006 through 2013-2014 academic years from a national convenience sample of high schools participating in the National High School Sports-Related Injury Surveillance Study (High School Reporting Information Online [RIO]) were analyzed. Results: Certified athletic trainers participating in High School RIO reported 115 of 1246 (9.2%) elbow injuries as elbow dislocations. A total of 30, 415, 179 athlete exposures (AEs) were reported during the study period, resulting in a dislocation rate of 0.38 per 100, 000 AEs. The majority of the dislocations resulted from boys' wrestling (46.1%) and football (37.4%). Elbow dislocation rates were higher in competition than in practice. Also, 91.3% of dislocations occurred in boys' sports. Among both boys (60.4%) and girls (88.9%), the majority of injuries occurred during varsity sports activities. Contact with another person was the most common injury mechanism (46.9%), followed by contact with the playing surface (46.0%). Dislocations more commonly resulted in removal from play for more than 3 weeks (23.4% vs 6.9%, respectively) or medical disqualification (36.9% vs 7.0%, respectively) compared with other elbow injuries. Dislocations were also more likely to result in surgical treatment than other elbow injuries (13.6% vs 4.7%, respectively). Conclusion: In high school athletes, elbow dislocations result in longer removal from play and are more likely to require surgical treatment than nondislocation-associated elbow injuries. Rates and patterns of elbow dislocations vary by sport. In high-risk sports, focused sport-specific prevention strategies may help to decrease the rates and severity of elbow dislocation injuries.